Utilizing Canva Application Training to Improve Skills and Product Sales in Micro Small Medium Enterprises (MSMEs) East Java - Sofyanto Tri Sunarto; Pompong B. Setiadi (Ilomata International Journal of Management, 2023)
Micro, Small and Medium Enterprises (MSMEs) are economic businesses in the field of sales or trade that are managed by individuals or business entities. The existence of MSMEs in the technological era needs to utilize applications that can support sales. Canva is a design app that can be used to support sales. Canva's role in Micro, Small and Medium Enterprises (MSMEs) is expected to be an application that makes it easier for actors to market their selling products. This study aims to determine the effect of Canva training on improving the skills and sales of Micro, Small and Medium Enterprises (MSMEs). The approach method used in the implementation of this training activity includes monological and dialogic methods. Based on the results of the study, training on using the Canva application to increase sales and skills has a positive effect on MSME owners. This is due to the use of the Canva application which is easily understood by all people and the costs incurred are not much.